(untitled) (Archives of Mechanics - Test, 2019)
Secondary flow features and total pressure losses by means of the total pressure loss coefficient are discussed in an entrance duct, named a turbine central frame (TCF), to a four-stage low-pressure turbine (LPT) of aero-engine. The massaveraged total pressure losses are also analysed at outlets from selected components of the low-pressure turbine. The Reynolds-averaged Navier–Stokes (RANS) technique has been employed for prediction of mean flow characteristics. The numerical results are compared with experimental data obtained in Polonia Aero Lab in Zielonka (Poland). Good agreement is obtained between measured and predicted global flow characteristics and the pressure coefficient on a surface of an inlet guide vane. The high values of the loss coefficient are observed at endwalls, in cores of streamwiseoriented vortex structures near to the endwalls and in the wakes behind the vanes. It is found that the endwall losses contribute by far the most to the total losses at the outlets from the turbine central frame and first vane-row and they become lower at an outlet f rom the first blade-row and at outlets form consecutive vane- and blade-rows.